Morphometric Study of Hyssopus Ambiguus Growing in the Territory of Central Kazakhstan - Lakomkina, Y.V.; Ishmuratova, M.Y.; Atazhanova, G.A. (OnLine Journal of Biological Sciences, 2022)
The article presents the results of the study of Hyssopus ambiguus herb, collected on the territory of Central Kazakhstan. We obtained data on diagnostic features of the studied species at morphological and anatomical levels. The purpose of the study is to determine the macro-and microscopic diagnostic features of the above-ground part of Hyssopus ambiguus. Materials and Methods: Raw material was collected on the territory of the Republic of Kazakhstan, Karaganda region. The microscopic and morphological studies were carried out according to the methods of the Republic of Kazakhstan State Pharmacopoeia (RKSP) using a Biomed-4 light microscope and a Levenhuk macroscope. Results: The main diagnostic features of Hyssopus ambiguus had been determined: Trichomas and essential oil glandules. Analysis of the anatomical and morphological features of leaves, shoots, and sepals was made; the characteristics of essential oil glandules were described. During the morphological and anatomical study of Hyssopus ambiguus, the diagnostically significant macro-and microscopic features of raw materials were identified and biometric characteristics were established. The experimental data allowed us to confirm the authenticity, identification, and standardization of the above-ground part of Hyssopus ambiguus.
Keywords: Hyssopus Ambiguus; Medical Plant; Macro-and Microscopic Diagnostic Features; Morphological and Anatomical Analysis